Disasters triggered by natural hazards and terrorism: A bibliometric network analysis into the intellectual structure of a cross-disciplinary research field - Joe Y. Battikh; Virginia Bodolica; Michael O. Wood (International Journal of Disaster Risk Reduction, 2022)
The relationship between disasters triggered by natural hazards (DTNH) and terrorism is attracting renewed public and academic interest. This review article aims to unveil the key areas of focus and assess the structure of the network of scholars along with the academic communities that are producing research on the topic. We applied term co-occurrences and co-citation network analysis methodologies to a sample of 1027 academic documents on DTNH and terrorism that were published over a four-decade period. Two areas of focus (security and trauma) and four scholarly communities (political studies, economics, psychology, and sociology) emerged at the juncture of DTNH and terrorism. Due to an observed lack of collaboration between select communities, a promising future research agenda is proposed for achieving knowledge cross-fertilization and developing a truly cross-disciplinary research field. As the increasing occurrence of DTNH makes the stricken regions more vulnerable to terrorist acts, this literature review is timely and critical for cumulative knowledge building on DTNH and terrorism.